MILITARY «BAGRATION» OPERATION AND LIBERATION OF BELARUS FROM GERMAN FASCIST INVADERS - K. I. Balandin (Наука и техника)
The paper considers preparation procedure and accomplishment of the «Bagration» operation. Role of interaction of three Belarussian and the 1-st Baltic Fronts with members of underground organizations and guerilla formations in the defeat of hostile forces is given in the paper. The paper also shows military and political significance of the Republic liberation in 1944.